Decoding the Final Sermon: Speech Acts and Islamic Imperatives in the Hadith of Hajj al-Wada' - Warsito, Loekisno Choiril; Umar Faruq (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2023)
The hadith concerning Hajj al-wada’, being the final utterance of Prophet Muhammad, has garnered significant attention from Hadith scholars, prompting various analyses of both its chain of narrators (sanad) and its content (matn). Focusing particularly on the matn aspect, scholars seek to delve into the deeper meaning embedded within the expressions or verbiage of the hadith, necessitating a thorough linguistic examination. This endeavor has given rise to the field of ma‘āni al-hadith, which centers its inquiry on the semantic nuances inherent within the text, whether textual or contextual. Within this contextual realm, pragmatic aspects take precedence, wherein the matn of the hadith is scrutinized through the lens of speech acts. In this article, we aim to explore the hadith of Hajj al-wada’ through the prism of one such pragmatic linguistic aspect: speech acts. This approach fundamentally analyzes the utterances or expressions -in this case, the matanof hadith hajj al-wada’- in light of the speaker’s and listener’s actions, encompassing locutionary, illocutionary, and perlocutionary acts. Through this investigation, we endeavor to illuminate the deeper layers of meaning embedded within this seminal hadith.